Archaeosomes and Gas Vesicles as Tools for Vaccine Development - Adamiak, Natalia; Krawczyk, Krzysztof T.; Locht, Camille; Kowalewicz-Kulbat, Magdalena (Frontiers in Immunology, 2021)
Archaea are prokaryotic organisms that were classified as a new domain in 1990. Archaeal cellular components and metabolites have found various applications in the pharmaceutical industry. Some archaea produce archaeosomes, a new family of liposomes that exhibit high stability to temperatures, pH and oxidative conditions. Additionally, archaeosomes can be efficient antigen carriers and adjuvants promoting humoral and cellular immune responses. Some archaea produce gas vesicles, which are nanoparticles released by the archaea that increase the buoyancy of the cells and facilitate an upward flotation in water columns. Purified gas vesicles display a great potential for bioengineering, due to their high stability, immunogenicity and uptake across cell membranes. Both archaeosomes and archaeal gas vesicles are attractive tools for the development of novel drug and vaccine carriers to control various diseases. In this review we discuss the current knowledge on production, preparation methods and potential applications of archaeosomes and gas vesicles as carriers for vaccines. We give an overview of the traditional structures of these carriers and their modifications. A comparative analysis of both vaccine delivery systems, including their advantages and limitations of their use, is provided. Gas vesicle- and archaeosome-based vaccines may be powerful next-generation tools for the prevention and treatment of a wide variety of infectious and non-infectious diseases.